THE IMPACT OF CROSS-BORDER MIGRATION ON LABOUR MARKETS IN BORDER REGIONS - Melyana R Pugu; Diego Romario De Fretes; Erwin (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The flow of labor migration indicates low employment opportunities in the country, thus encouraging them to trade in neighboring countries, which offer market opportunities that are more promising for prosperity. In this context, cross-border migration in border areas is seen as positive because it can reduce the problem of unemployment in the country and can improve the economic life of the community. Encourage increased productivity and innovation. Another thing that can happen to cross- border migration is that migration can create competition in the workforce. Workers may compete with the local workforce for low- paying jobs, this can result in pressure on wages and working conditions. The research was carried out using the literature study method. A literature review was used to collect data and information regarding the influence of cross-border migration on the labor market in border areas. This research discusses the definition of cross-border migration, the different styles and types of cross-border migration, the influence of cross-border migration on the labor market, and the factors that influence cross-border migration.